1998
DOI: 10.1080/00224549809600391
|View full text |Cite
|
Sign up to set email alerts
|

Blacks' and Whites' Perceptions of Interracial and Intraracial Date Rape

Abstract: The prevalence of rape myths contributes to victims' reluctance to report rapes. Black (n = 30) and White (n = 96) U.S. college students responded to the Rape Myth Scale (Burt, 1980) and read a scenario of an acquaintance rape; the race of the perpetrator and victim (Black or White) were varied. The respondents assessed the victim's and perpetrator's responsibility and evaluated the incident. As hypothesized, the respondents with strong beliefs in rape myths were more tolerant of the rapist and less tolerant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 4 publications
2
47
2
Order By: Relevance
“…Most past research has shown that non-White participants are more likely to endorse rape myths than White participants (e.g., Jimenez and Abreu 2003;Varelas and Foley 1998), although Carmody and Washington (2001) did not find a difference in rape myth endorsement between black and white women. Contradictory findings and the general neglect of non-white participants in research underscore the need to investigate the impact of participant race in future studies.…”
Section: Limitationsmentioning
confidence: 95%
“…Most past research has shown that non-White participants are more likely to endorse rape myths than White participants (e.g., Jimenez and Abreu 2003;Varelas and Foley 1998), although Carmody and Washington (2001) did not find a difference in rape myth endorsement between black and white women. Contradictory findings and the general neglect of non-white participants in research underscore the need to investigate the impact of participant race in future studies.…”
Section: Limitationsmentioning
confidence: 95%
“…These investigations also suggest the interracial or intraracial configurations of Caucasian-and African-American sexual assaults influence perceptions of assailants and victims. Generally, observers seem less empathic toward African-than to CaucasianAmeican victims who are involved in dating relationships (vs. stranger assaults) and attribute more responsibility to African-than to Caucasian-American perpetrators (Varelas and Foley 1998;Willis 1992). Howard (1988) evaluated the influence of essentialist characterizations, cultural impacts, and structural influences on African-and Caucasian-American adolescents' attitudes on heterosexual relationships and sexual assault.…”
Section: Ethnicity and Rape Attitudesmentioning
confidence: 98%
“…Previous research on date rape has traditionally focused on (a) how perceiver characteristics affect perceptions, and (b) how manipulated aspects of date rape scenarios affect perceptions. Regarding perceiver characteristics, one of the most consistent findings has been that men assign more blame to victims, and less blame to perpetrators, than women (Bascow & Minieri, 2010;Bell, Kuriloff, & Lottes, 1994;Black & Gold, 2008;Grubb & Harrower, 2009;Hannon, Kuntz, Van Laar, Williams, & Hall, 1996;Hattery Freetly & Kane 1995;Monson, Langhinrichsen-Rohling, & Binderup 2000;Varelas & Foley, 1998;Workman & Freeburg, 1999). Race also plays a significant role in how individuals perceive date rape.…”
Section: Past Research On Perceptions Of Date Rape and Sexual Coercionmentioning
confidence: 99%
“…Race also plays a significant role in how individuals perceive date rape. Varelas and Foley (1998) found that White participants were more likely than Black participants to attribute responsibility to perpetrators and to believe victims should notify authorities. Personal ideologies further influence date rape perceptions.…”
Section: Past Research On Perceptions Of Date Rape and Sexual Coercionmentioning
confidence: 99%